2010
DOI: 10.4149/neo_2010_02_145
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation in patients with advanced gastric cancer

Abstract: The aim of this study was to evaluate platelet activation in gastric cancer patients with regard to histopathological classification and the presence of distant metastases, by using platelet morphological parameters: MPV, L-PLT, MPC, as well as quantitative evaluation of surface receptor expression: CD41a, CD61, CD42b, CD62P, by flow cytometry at the resting state and after TRAP activation. In gastric cancer patients higher values of MPV and LP, as well as decreased MPC values were determined. Quantitative eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 13 publications
(38 reference statements)
0
51
0
1
Order By: Relevance
“…Assessment of the MPV in patients with malignant tumours has recently attracted substantial interest even though some results have been controversial. For instance, previous studies have reported that the MPV was higher in patients with gastric cancer than in control patients and that the MPV/PC (platelet count) ratio was meaningfully increased in patients with hepatocellular carcinoma [29, 30]. In addition, published research has reported a significant correlation between high MPV and advanced cancer, such as gastric cancer [16], hepatocellular carcinoma [30], endometrial cancer [15], breast cancer [31], and colon cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the MPV in patients with malignant tumours has recently attracted substantial interest even though some results have been controversial. For instance, previous studies have reported that the MPV was higher in patients with gastric cancer than in control patients and that the MPV/PC (platelet count) ratio was meaningfully increased in patients with hepatocellular carcinoma [29, 30]. In addition, published research has reported a significant correlation between high MPV and advanced cancer, such as gastric cancer [16], hepatocellular carcinoma [30], endometrial cancer [15], breast cancer [31], and colon cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that MPV could be used to predict the onset of venous thromboembolism and arterial thrombosis (Braekkan et al, 2010). Furthermore, MPV may be a diagnosis marker in hepatocellular carcinoma, pancreatic adenocarcinoma, and gastric cancer (Osada et al, 2010;Karaman et al, 2011;Kurt et al, 2012).…”
Section: * Xi-shan Wang 1 *mentioning
confidence: 99%
“…In cancer patients, sCD40L is more likely derived from activated platelets than from T-cells [15]; therefore, sCD40L can affect cancer development and progression by inducing thrombotic reactions and releasing angiogenesis-associated cytokines. This idea is supported by evidence that cancer patients, including those with pancreatic ductal adenocarcinoma (PDAC), have significant platelet activation [16-18]. Widespread expression of CD40 in human carcinomas also supports the role of this ligand in cancer pathogenesis [19].…”
Section: Introductionmentioning
confidence: 97%